Evaluation of the inhaled dose across different microenvironments - Borghi, F; Cattaneo, A; Spinazzè, A; Manno, A; Rovelli, S; Campagnolo, D; Vicenzi, M; Mariani, J; Bollati, V; Cavallo, D M (IOP conference series. Earth and environmental science, 2019)
The principal aim of the INSIDE project (INdividual air pollution exposure, extracellular vescicles SIgnaling and hypertensive disorder DEvelopment in pregnancy) is to assess the molecular effects of environmental exposure to airborne particulate matter (PM) of susceptible subject. Different approaches are considered to evaluate these effects, including an exposure-effect study performed on a selected population. The short-term exposure to different pollutants (PM and NO2) was evaluated considering 51 subjects recruited from October 2017 to April 2018. Each subject was asked to carry personal instruments for few hours before a clinical evaluation (blood and cardiological examination) from home to hospital. Instruments used in the study were: (I) CairClip - CairPol (NO2) and (II) Aerocet 831 - Aerosol Mass Monitor, Met One Instruments (size-fractionated PM). Moreover, a (III) smartphone with a GPS application and a (IV) Time Activity Diary (TAD) were used in this study to acquire information about the microenvironments (MEs) visited by subjects during the monitoring sessions. The experimental design of the project allowed to further investigate issues related to the mode of exposure: through the analysis of TADs and GPS data, it was possible to document the time spent by each subject in the different MEs and characterize the average exposure and inhaled dose associated to different MEs. The microenvironmental inhaled dose of pollutants was estimated considering the average exposure to PM and NO2, the time spent across these MEs and the specific ventilation rate of each subject. Moreover, to understand which of these parameters has the major impact of the dose model, a sensitivity analysis was performed, on the total and on the MEs dataset.